International Criminal Court Takes Important Step in DR Congo - Human Rights Watch (Human Rights Watch, 2024)
On October 14, the International Criminal Court (ICC) prosecutor, Karim A. A. Khan, announced that his office would step up investigative efforts in the Democratic Republic of Congo, focusing in particular on crimes committed in the North Kivu province since January 2022.